D7.3 Proceedings of the Second DREAM-GO Workshop: Real-Time Demand Response and Intelligent Direct Load Control - Vale, Zita (2021)
Proceedings of the Second DREAM-GO Workshop Real-Time Demand Response and Intelligent Direct Load Control